Comparative Investigation of the Effect of Electromagnetic Radiation at Frequencies of 51.8 and 53 GHz on Arthrospira platensis and Parachlorella kessleri (Journal of Innovative Solutions for Eco-Environmental Sustainability, 2025)
Electromagnetic radiation (EMR) plays a significant role in telecommunications, medicine, science, and technology, and affects natural processes and human health. The impact of extremely high-frequency EMR on microorganisms is currently a prominent area of research, as microorganisms in various ecological environments are exposed to differing levels of EMR. This study examines the effects of low-intensity EMR at frequencies of 51.8 GHz and 53 GHz on growth parameters, including cell morphology, growth rate, biomass yield, and the composition of photosynthetic pigments, of cyanobacterium Arthrospira platensis Pc-005 and green alga Parachlorella kessleri MDC6524 (Microbial Depository Center, NAS, Yerevan, Armenia). Exposure to EMR at frequencies of 51.8 and 53 GHz increased biomass yield in both cultures by ~40% compared to non-irradiated control cells. This indicates that EMR can notably enhance A. platensis and P. kessleri productivity, potentially leading to more efficient and cost-effective cultivation. EMR exposure also increased the content of pigments such as chlorophyll a, phycocyanin, and carotenoids in A. platensis, as well as chlorophylls a and b, and carotenoids in P. kessleri, compared to the control samples. Morphological analysis revealed that short-term EMR exposure increased filament size and caused slight curvature in A. platensis, whereas a 60-minute exposure predominantly resulted in short, wrinkled trichomes and a loss of structural definition. In the case of P. kessleri, short-term irradiation caused no noticeable changes; however, after 60-minute exposure at 53 GHz, the cells appeared larger and exhibited a bright green color. These morphological changes correlate with increased pigment content and biomass, indicating enhanced photosynthetic activity under EMR exposure. Thus, the results suggest that extremely high-frequency EMR can serve as an effective tool for optimizing microalgae cultivation and increasing their productivity.
Keywords: extremely high frequency electromagnetic irradiation; microalgae; growth properties; photosynthetic pigments; morphology